2022
DOI: 10.1002/1873-3468.14510
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bond formation and redox regulation in the Golgi apparatus

Abstract: Formation of disulfide bonds in secreted and cell‐surface proteins involves numerous enzymes and chaperones abundant in the endoplasmic reticulum (ER), the first and main site for disulfide bonding in the secretory pathway. Although the Golgi apparatus is the major station after the ER, little is known about thiol‐based redox activity in this compartment. QSOX1 and its paralog QSOX2 are the only known Golgi‐resident enzymes catalyzing disulfide bonding. The localization of disulfide catalysts in an organelle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…We found that within MSC subpopulations, Tead2 was enriched in clusters 1, 2, 3, 4, 8, and 9, while Atf3 was weakly expressed in clusters 3, 4, and 9. Qsox1 encodes an enzyme that catalyzes disulfide bond formation and is involved in redox regulation (Reznik and Fass, 2022). In our analysis, Qsox1 was expressed in MSC clusters 1, 2, 3, 4, 8, 9, and 10; Runx2 in cluster 1, 2, 3, 4, 7, 8, and 9; and Maf in clusters 1, 2, 3, 4, 8, and 10.…”
Section: Single-cell Rna Expression Profile Of Interacting Partners O...mentioning
confidence: 75%
“…We found that within MSC subpopulations, Tead2 was enriched in clusters 1, 2, 3, 4, 8, and 9, while Atf3 was weakly expressed in clusters 3, 4, and 9. Qsox1 encodes an enzyme that catalyzes disulfide bond formation and is involved in redox regulation (Reznik and Fass, 2022). In our analysis, Qsox1 was expressed in MSC clusters 1, 2, 3, 4, 8, 9, and 10; Runx2 in cluster 1, 2, 3, 4, 7, 8, and 9; and Maf in clusters 1, 2, 3, 4, 8, and 10.…”
Section: Single-cell Rna Expression Profile Of Interacting Partners O...mentioning
confidence: 75%
“…Moreover, the gene-based scoring system can forecast NAFLD progression, facilitating early interventions for patients at risk of advancing to severe disease stages.Previous studies have explored the relationship between QSOX1, IL1RAP, and NAFLD or steatosis(16, 61). QSOX1 has been suggested as a potential diagnostic biomarker for NAFLD, playing a significant role in lipid metabolism as an enzyme expressed in various tissues, particularly in quiescent fibroblasts (18, 62, 63). IL1RAP is localized in vesicles and cytosol, and it is secreted into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, through an analysis of the integrated large-scale scRNA and snRNA sequencing data to interpret potential biomarkers, we shed light on previously undiscovered facets of NAFLD pathogenesis and intercellular crosstalk. QSOX1 and its less common variant, QSOX2, are unique among sulfhydryl oxidases because they are specifically found in the Golgi apparatus of animal cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…QSOX1 and its less common variant, QSOX2, are unique among sulfhydryl oxidases because they are specifically found in the Golgi apparatus of animal cells (28). Studies found elevated expression of QSOX1 in quiescent fibroblasts, and it is also released into the bloodstream (29, 30).…”
Section: Discussionmentioning
confidence: 99%